APLIKASI PEMBELAJARAN CONVERSATION UNTUK ANAK DENGAN MENGGUNAKAN METODE COMPUTER BASED INSTRUCTION - Juniyus Simarmata (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
The lack of practice Conversation also causes learning English to be less attractive to somepeople, especially students. With the practice, children's English skills will be honed so that they arefinally used to and trained in English. One way to overcome this problem is the use of conversationlearning applications that can be run on a computer through a Compact Disk (CD). The materialpresented in this application is listening, practice and quizzes. This application was designed usingthe CBI method, developed using Macromedia Flash8 applications. From the results of the testsconducted, it can be concluded that the system can be run properly and function as expected. Forfurther development it is expected that this application can be reproduced content or material contentto make it better and more interesting.